Reflectivity of Cholesteric Liquid Crystals with an Anisotropic Defect Layer Inside - Dariusz Grzelczyk; Jan Awrejcewicz (Photonics, 2020)
In this study, first, we numerically investigated the reflectivity of a cholesteric liquid crystal with an anisotropic defect layer inside. To model optical phenomena in the examined system, a 4 × 4 matrix method was employed. The tests were carried out for different thicknesses of the whole system, different thicknesses of the defect layer, as well as different defect layer locations inside the cell. Next, a cholesteric liquid crystal comprising a defect layer and held between two parallel electrical conductors was also considered. In this case, the optical properties of the system could also be adjusted by an external applied electric field. Some interesting simulation results of the reflection coefficient (i.e., the fraction of electromagnetic energy reflected) were obtained, illustrated, and discussed. The simulation results showed a significant influence of both the defect and the external electric field on the selective reflection phenomenon, and the possibility of controlling the shape of the reflection spectrum. Finally, some potential applications of the analyzed optical system were discussed.